Resilience in the Caribbean - Natural Hazards Exposure Assessment and Areas for Future Work : 360° Resilience Background Paper - Schweikert, A.E. (World Bank, Washington, DC, 2021)
Evaluating the resilience of critical infrastructure systems (power, transport and water sectors) in the Caribbean requires geospatial data on infrastructure, hazard frequency, fragility, and downstream impact modeling. Ideally, resilience analyses can inform decision makers about their most vulnerable assets, losses that would have the largest impacts, and how to prioritize funding in the reality of limited budgets. The assessment of multiple assets within each sector is important to understand interdependencies and how loss of one system (e.g. transmission and distribution) can affect others (e.g. business operations). The interdependency between systems is also important to inform holistic planning. For example, roads are a key asset for water delivery in times of drought or pipe failure and for travel to hospitals or other critical facilities. Taking a systems perspective caN help resiliency planning by identifying the most vulnerable and important assets to reduce repeated failure of critical assets. In many countries with high exposure to natural hazards (such as small island states in the Caribbean), a recovery trap is caused by continued repair of repeatedly damaged assets. Climate change may cause this to worsen as the intensity and/or frequency of events including hurricanes, coastal surge, flood and heatwaves changes.